PENGARUH PENGEMBALIAN KREDIT TERHADAP TINGKAT PROFITABILITAS DI PT BPR TUAH NEGERI PEKANBARU - Resti Indrahayu Indrahayu; Henny Indrawati Indrawati; Gani Haryana Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This study aims to determine the effect of the repayment of the level of profitability in the PT BPR Tuah Negeri Mandiri  Pekanbaru. This research in the BPR Tuah Negeri Mandiri  Pekanbaru from March 2015 until June 2015. The methode research used is descriptive quantitative methode. Population is financial statement and rcap report loans per type of use PT BPR Tuah Negeri Mandiri  Pekanbaru and a sample financial statement and recapreport loans per type of use PT BPR Tuah Negeri Mandiri  Pekanbaru periode January 2012 until December 2014. Data analysis technique used is simple linear regression. The result showed that loans repayments affect the level of profitability. This is based on the result of analyzes, calculations showed t hitung > t tabel (5,347>2,040). So it can be concluded that the loans repayment affect the level of profitaqbility with a contribution 45,7% and the remaining 54,3% is affect by others variabels unobserved variables like interest income, credit provision and others. Keywords: effect, credit refund, level of profitability